PEMBERDAYAAN KELOMPOK TANI TERNAK DI DESA CAMPLONG II, KABUPATEN KUPANG DALAM KERANGKA PENCEGAHAN PENYAKIT MENULAR PADA TERNAK MELALUI PEMANFAAT DISINFEKTAN YANG AMAN DAN TEPAT - Maria Aega Gelolodo; Novalino Harold Geoffrey Kallau; Larry Richard Wellem Toha; Julianty Almet; Dewi Fesbayanti Lestari Djungu; Diana Agustiani Wuri; Elisabet Tangkonda; Maxs Urias Ebenhaizar Sanam; Annytha Ina Rohi Detha; Aji Winarso (Jurnal Media Tropika, 2022)
Infectious diseases in livestock are a major issue in the global livestock industry. Kupang Regency is one of the livestock warehousing regions in NTT, and it also has issues every year owing to infectious diseases that target many species of livestock in the district, particularly cattle and pigs, which are the backbone of Kupang Regency. Recognizing the importance of livestock for the socioeconomic life of the local community and the magnitude of the effects that infectious diseases can have on livestock, one of the important strategic steps that must be taken is to empower livestock farmer groups in the effort to prevent infectious diseases in livestock, particularly in the safe and appropriate use of disinfectants. This community service was carried out at Camplong II Village, Kupang Regency, and three groups of livestock farmers from the village area participated. Counseling, interactive dialogues with livestock farmer groups, and demonstration on the use of appropriate and correct disinfectants were among the activities carried out. This activity revealed that many members of livestock farmer groups are still uninformed of the role and usage of disinfectants in the prevention of infectious diseases in their livestock. At the end of the program, the community learnt to distinguish different types of disinfectants and their applications in the farming managment.